Trends and determinants of maternal health services utilization in India from 2015 to 2021 - Wapangjungla Longchar; Prakash Babu Kodali; Sibasis Hense (Scientific Reports)
Abstract Continuum of care (CoC) in maternal health services refers to a pathway spanning from pregnancy and childbirth to post-pregnancy, covering routine antenatal care (ANC), institutional delivery (ID), and post-natal services (PNC). The current study aims to investigate the distribution, trends, dropouts, and determinants of maternal health services (ANC, ID, and PNC) utilization along the CoC pathway using NFHS-4 and NFHS-5 datasets from 2015 to 2021. The binary logistic regression examined the association between the continuum of maternal health services utilization and the predictor variables. The complete CoC utilization was 50% during NFHS 5, an 11.3%-point increase from NFHS-4. During the same period, the largest dropout was in the uptake of full ANC (41.5%). Odds of completing CoC were higher among women aged 25–34 (AOR:1.18; 95% CI: 1.09–1.27), with higher education (AOR:1.74; 95% CI: 1.58–1.92), urban women (AOR:1.09; 95% CI:1.01–1.19), in richer household (AOR: 1.42; 95% CI: 1.29–1.56), and with health insurance (AOR: 1.24; 95% CI: 1.15–1.35). Strengthening the public health system and addressing bottlenecks of government maternal health schemes remains an important consideration for improving the continuum of maternal care in India. Context-specific multi-sectoral strategies may be leveraged to increase the uptake of maternal health services, especially in high-focus states.